Influência do treinamento resistido na atividade fagocítica de monócitos e neutrófilos em mulheres idosas - Bartholomeu Neto, João (2018)
Projections of the increase in absolute and relative numbers of elderly represent new challenges for public health. Aging is accompanied by gradual decline of physiological functions, immune function and muscle strength. In this way, the elderly is more susceptible to sarcopenia, osteoporosis, cancer and cardiovascular, metabolic and neurodegenerative diseases. Resistance Training (RT) has been shown to be an important intervention for increased muscle strength and decreased chronic inflammation in the elderly. However, little is known about the influence of RT on the functional response of cells that constitute the first line of defense during immunosenescence. In this sense, the present study aimed to investigate an association between RT adaptations induced by a program and a functional response of circulating phagocytes in elderly. The present cross-sectional study was composed of 54 elderly women, 71.3 ± 6.3 years, apparently healthy, non-institutionalized and divided into two distinct groups: Trained (n = 28) and Sedentary (n = 26). The elderly of the Trained group were participants of a RT program for 8.6 ± 0.3 months and performed a training consisting of 12 exercises, 3 sessions weekly, with intensity of 70% of a maximum repetition, while the Sedentary group did not participate of any physical activity program during the same period. Body mass, height, body mass index, waisthip ratio, fat free mass and fat mass were evaluated. The total energy intake and macronutrients in the usual diet were assessed. TNF-a, IL-6 and IGF-1 analyzes, total and differential leukocyte count, monocyte or neutrophil phagocytosis test, phagocytosis index (IF) and microbicidal activity of phagocytes were performed. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS) program and considered statistically significant P <0.05 for two-tailed tests. The results show that the IF of neutrophils (but not of monocytes) in the Trained group was significantly higher (! <0.001, effect size, (") = 0.90, 95% CI: [0.75-1.04]) compared to that in Sedentary group. In contrast, the microbicidal activity of phagocytic cells was not significantly influenced by RT. Also, total energy and carbohydrate intake, as well as serum levels of IL-6, had a significant influence on the phagocytic activity of neutrophils (! = 0.04), being considered in the model. Multivariate regression identified the physical condition of the subject (β = 0.425; ! = 0.01) as a significant predictor of the IF. In conclusion, the circulating neutrophils of elderly women who had TR showed higher phagocytic activity, whereas microbicidal activity did not present a statistically significant difference between groups, demonstrating a positive effect of RT in the first line of defense of the organism.